2018
DOI: 10.12659/aot.910008
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation Using an Isolated Reperfusion Model for Porcine Liver Donated After Cardiac Death Preserved with Oxygenated Hypothermic Machine Perfusion

Abstract: BackgroundMachine perfusion techniques offer a solution to the serious organ shortage. However, to assess the effects of machine perfusion, many detailed studies are required. In this study, an ex vivo reperfusion model using diluted autologous blood was confirmed to evaluate the utility of machine preservation for livers donated after cardiac death (DCD). In particular, beneficial effects of the oxygenated hypothermic machine perfusion (HMP) for DCD porcine livers are evaluated.Material/MethodsPorcine livers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…This review demonstrated that the Hct in the experiment is about 20%, but there are some that are higher or lower than that. Yoshikawa et al [19,34] showed the effectiveness of our evaluation system. Qiang Liu et al[35].…”
Section: Discussionmentioning
confidence: 94%
“…This review demonstrated that the Hct in the experiment is about 20%, but there are some that are higher or lower than that. Yoshikawa et al [19,34] showed the effectiveness of our evaluation system. Qiang Liu et al[35].…”
Section: Discussionmentioning
confidence: 94%
“…The livers were evaluated by reperfusion with oxygenated diluted autologous blood at 38 °C rather than after transplantation. We reported that the ERM can be useful for evaluating MP utility 19 , 20 . This isolated ERM can reduce the need for animal transplantation experiments and the technical bias associated with the actual transplantation operation, and facilitate observation of hemodynamic changes (perfusion area and vascular pressure resistance) during reperfusion.…”
Section: Discussionmentioning
confidence: 99%
“…After preservation, the liver function was evaluated using an isolated liver reperfusion model 6 , 19 , 20 . This system consisted of HA and PV perfusion circuits, with each circuit comprising a roller-type pump (Masterflex 7520-40; Cole-Parmer, Bunker Court, IL, USA), electrical flow meter (VN05; Aichi Tokei, Aichi, Japan for the PV; FD-SS02; Keyence, Osaka, Japan for the HA), ceramic capacitive pressure sensor (KL76; Nagano Keiki, Nagano, Japan), and an air trap developed in-house.…”
Section: Methodsmentioning
confidence: 99%
“…Machine perfusion was developed to improve the quality of preservation for donor grafts 8 , 18 21 . Two major perfusion strategies, hypothermic and normothermic techniques, are currently used in clinical settings 1 , 6 , 22 24 .…”
Section: Discussionmentioning
confidence: 99%